The Influence of Brand Image, Consumer Trust, and Promotion on Daihatsu Purchase Intentions: Case Study of Safety Test Counterfeiting Standards - Setiyawan, Demas Andhika; Boerhan, Bernardus (Journal of Current Research In Multidisciplinary, 2024)
This research aims to analyze the influence of brand image, consumer trust, and promotion on purchase intentions. This research employs quantitative methods and operates as a causal study. A questionnaire was used to collect data. The hypothesis results indicate that brand image does not exert a positive influence on purchase intentions. The negative impact of the safety test falsification issue may have obscured the previously formed positive image of the brand, making consumers' perceptions of it less significant in shaping their purchase intentions. Research has proven that consumer trust positively influences purchase intentions. This indicates that consumer trust is a critical factor that can influence their purchasing decisions. Consumers who feel confident in the integrity and reliability of products tend to have higher purchase intentions, even if negative issues arise. Promotions also have a positive influence on purchase intention. This shows that effective promotional efforts can increase consumer purchasing intentions. By providing clear information and convincing consumers about the company's corrective steps, the right promotional strategy can help mitigate the negative impact of safety test falsification. Overall, research shows that consumer trust and effective promotional strategies significantly influence purchase intentions, even though brand image does not have a positive influence in this case. Therefore, to rebuild and increase consumer purchasing intentions, companies need to focus on efforts to build consumer trust and develop effective promotional strategies.